FRI0245 RHEUMATOID FACTOR IN IGA, IGG AND IGM IMMUNOGLOBULIN CLASES IN PRIMARY SJöGREN'S SYNDROME. (June 2019) - Maślińska, Maria; Dmowska-Chalaba, Joanna; Mańczak, Małgorzata; Shen, Long; Suresh, Lakshmanan; Kwiatkowska, Brygida
Abstract : Background: Primary Sjögren's syndrome (pSS) is an autoimmune disease with the autoantibodies overproduction, including rheumatoid factors (RF). An association of RFs with the disease activity has been already described, with RFs in IgA, IgG immunoglobulin classes suggested as potential biomarkers of immunological/clinical pSS features. Objectives: Examining correlations of RF in IgM, IgA and IgG immunoglobulin classes with other autoantibodies, dry eye tests and histopathological assessment (focus score) of salivary gland inflammation. Methods: We studied 76 patients, mean age 53 (SD=13); (67Female/9Male) with pSS diagnosis (criteria ACR/Eular 2017); mean disease duration from diagnosis 2, 24 year. Laboratory tests performed: ESR, C-reactive protein(CRP), concentrations of gamma globulins (g/dl), RF serum concentration assessed using ImmuLisa Enhanced™ RF IgA, IgG, IgM Antibody ELISA IMMCO Diagnostics, Inc. As positive result of the RF-IgA and RF-IgG concentration > 25 EU/mL was considered, as positive RF-IgM > 12, 5 EU/mL; a highly positive result set as > 100 EU/mL. Anti-Ro/SSA, and anti-La/SSB antibodies were detected by semiquantitative dot blot method. The eye dryness and keratoconjunctivitis sicca were confirmed with Schirmer's test (score of less than 5 mm/5') and the ocular staining score (OSS) using lissamine green and fluorescein staining and biopsy of minor salivary gland with the histopathological evaluation (focus score-FS). The study was approved by the proper ethics committee. Differences between groups were analyzed with U Mann-Whitney test (continuous variables). Correlations between quantative variables were assessed with the Spearman correlation coefficient. Statistical significance was set at p<0.05. Results: The detection of RF in examined sera: RF- IgA: positive(+) 66% (n=50), negative (-) 34%(n=26); highly positive (++) 51%(n=39); RF-IgG: + 55% (n=42), - 45%(n=34), ++ 9% (n=7); RF-IgM: + 88% (n=67), - 12%(n=9), ++ 55% (n=42). In comparison of patients' groups: i/RF-IgA (+) vs. RF-IgA(-) : no difference in term of FS, OSS and Schirmer's test; in RF-IgA(+) group significantly higher anti SS-A antibodies (p=0, 002); a significant difference in anti SS-A antibodies level (p=0.028) RF-IgA(++) and lower positive group (less than 100EU/mL); ii/RF-IgM(+) vs. RF-IgM(-): RF-IgM (+) significantly higher anti -SS-A antibodies (p=0.007); iii/RF-IgG (+) vs. RF-IgG(-): RF-IgG(+): RF-IgG(+) significantly higher anti SS-B antibodies (p=0.015). Positive correlation was found between: RF-IgA(+) and RF- IgG(+) (rho=0.647) and RF- IgM(+) (rho= 0.669); RF-IgG(+) and RF-IgM(-) (rho=0.429). Surprisingly no correlations found in studied group between concentrations of RF- IgA, IgG and IgM and WBC, C4, C3 complement component, FS, OSS, and Schirmer's test. Conclusion: 1. rheumatoid factors in main three classes of gammaglobulins, particularly RF-IgA, strongly associate with anti-SSA and anti-SSB autoantibodies production. 2. RF – IgM and RF- IgA dominate over RF- IgG in pSS. 3. both RF-IgA and RF-IgM may be used as diagnostic tool for pSS. 4. Further research is needed to distinguish activity and role of RF- IgA based upon its presence in serum vs. in saliva. References: [1] Peen E, Mellbye OJ, Haga HJ. IgA rheumatoid factor in primary Sjogren's syndrome. Scand J Rheumatol. 2009 Jan-Feb;38(1):46-9. [2] García-Carrasco M, Mendoza-Pinto C, Jiménez-Hernández C, Jiménez-Hernández M, Nava-Zavala A, Riebeling C. Serologic features of primary Sjögren's syndrome: clinical and prognostic correlation. Int J Clin Rheumatol. 2012;7(6):651-659. Disclosure of Interests: None declared